Rings, Igloos, and Pebbles of Salt Formed by Drying Saline Drops - Shin, Bongsu; Moon, Myoung-Woon; Kim, Ho-Young (AMER CHEMICAL SOC, 2014)
It is well-known that evaporation of sessile drops with suspended particles like colloids and coffee powders can yield a variety of two-dimensional patterns depending on the particle shapes and internal flow patterns. Here we show that ordered three-dimensional structures can be built via evaporation of saline drops on highly hydrophobic substrates like pristine PP (polypropylene) with micropores and nanostructured low-surface-energy PP. On pristine PP having a high contact angle but a large contact angle hysteresis (CAH) with water, either rings or igloos of salt are formed depending on the salt concentration and evaporation rate. On nanostructured low-surface-energy PP having extreme water repellency with a very low CAH, pebbles of salt are formed regardless of salt concentration and evaporation rate. These observations lead us to conclude that combined effects of solubility, evaporation rate, and mobility of the contact line determine the final three-dimensional shape of the salt precipitate.
Keywords: CONTACT-ANGLE HYSTERESIS; EVAPORATION STAINS; SURFACE; WATER